Upstream Gas Portfolio Optimization under Fiscal Rules and Uncertainty: A Systematic Review and Bibliometric Mapping - Naikosou, Marcelino Freitas; Adityawarman, Adityawarman; Guterres, Mario Viana; Mota, Teodoro Marcos; Samawi, Nabil Visi; Ariadji, Tutuka; Siagian, Utjok W. R.; Gunawan, Agus Yodi; Prenata, Danang Hayu; Saldanha, Estanislau de Sousa (International Journal of Energy Economics and Policy, 2026)
This study combines a systematic review (in accordance with PRISMA) and bibliometric mapping (VOSviewer & Bibliometrix) to explain how upstream gas portfolio decisions are optimized when fiscal rules limit annual cash flow. The Scopus 2005–2025 corpus of Title–Abstract–Keywords searches (1,149 records) confirm two pillars of the method: stochastic/robust optimization for portfolio sequencing and real options for flexibility in investment time and scale. Trend analysis, intellectual networks, and keyword evolution show the dominance of analytical-decision and reservoir planning themes; conversely, fiscal overlays such as withdrawal caps, cash-flow/budget constraints are still rarely formalized in mainstream models. The SLR synthesis shows that explicitly coding multi-period liquidity constraints materially changes project selection, sequencing, peak cash, and break-even timing compared to the baseline without constraints. The policy implication is a shift from hard caps to multi-period designed caps (with liquidity floors and countercyclical elements) integrated directly into the optimization framework. To balance value and fiscal stability, we recommend a gas-centric and modular portfolio that pairs ENPV with downside risk control objectives (e.g., CVaR/peak cash minimization). The main contribution of this study is to map fiscal gaps in the optimization literature and propose a research direction towards an integrated stochastic–real options framework with an overlay of fiscal rules that enables policy frontier reporting (value vs. stability).